(untitled) (Academicia Globe: Inderscience Research, 2023)
Despite the fact that pedagogues, psychologists and philosophers are still interested in the influence of the environment on the human personality, they have not come to a single opinion. Their views show more contradictions than commonality. Since the object of education is a person (student), first of all, it is appropriate to determine the concept of the person, then its formation and the place of education in it. The concept of personality is unique to a person. Man belongs to the most perfectly developed class of mammals. In this case, man appears as a biological species. As a biological species, a person has a number of characteristics: the structure of his organism (walking upright, the presence of movement organs, the brain and its development, eye, hair color, blood type, similarities and differences from his parents, higher nervous activity) and his mind with highly developed thinking ability. is described. But biological characteristics cannot fully characterize a person. Its essence is a human being, and in a human being, the social essence is determined. The essence of a person is evident in his personality.